PROSIDING SLAMET RIYADI CONFERENCE ON PUBLIC ADMINISTRATION (SRIPA) - Himadi Fisip (PROSIDING: SLAMET RIYADI CONFERENCE ON PUBLIC ADMINISTRATION (SRIPA), 2020)
PROSIDING SLAMET RIYADI CONFERENCE ON PUBLIC ADMINISTRATION (SRIPA)